A framework for designing mobile virtual training systems through virtual modeling technology - Wang, Xiangyu; Dunston, P. (Wiley, 2012)
Off-site and on-the-job training programs constitute the prevalent methods for training construction equipment operators in construction industry. Being time intensive, expensive, and potentially hazardous, these methods give novices a limited opportunity to experience real working conditions. Virtual technologies are envisaged to meet above stringent challenge. The classification scheme for categorizing virtual technologies into Augmented Reality, Augmented Virtuality, Virtual Reality, teleoperation, and simulator, is presented with a thorough state-of-the-art review. To carry out comparisons between different training schemes, a systematic taxonomy was formulated to identify some of the distinctions; it distinguishes between some of the constraints imposed by different training scenario environments and is applicable to the design of virtual training programs. A cognitive–motor spectrum was also developed for relating virtual technologies to transferred skills. The methods for measuring and evaluating the extent of skill transfer from virtual training program to real world performance were also discussed.